P0572ABSENCE OF RENAL FUNCTION RECOVERY AFTER AN ACUTE KIDNEY INJURY PREDICTS SHORT-TERM MORTALITY. (6th June 2020) - Quiroga, Borja; Sanz Sainz, Marta; Santos Sánchez-Rey, Begoña; Muñoz Ramos, Patricia; Ruano, Pablo
Abstract: Background and Aims: The incidence of acute kidney injury (AKI) during a hospitalization is frequent and worsen the prognosis. Recovery of renal function after AKI has been lightly studied and cut-off for establishing full recovery has not been determined. The aim of the present study is to evaluate the association between different degrees of renal function recovery after AKI and short-term mortality post-discharge. Method: This is a retrospective study that included all the AKI codified in the electronic records of our center in 2013 and 2014. We collect epidemiological data and comorbidities at baseline and laboratory values at admission and discharge. To analyze the impact of recovery of renal function after AKI we performed a univariate logistic regression with different cutoff of creatinine after 7 days of the AKI in comparison to baseline. We used the most sensitive cutoff to define recovery and evaluated associated factors (figure 1). Patients were followed during 30 days to assess associated factors to prognosis after AKI. Results: We included 1720 patients in this study. After the hospitalization due to AKI, 1194 (69%) entered in the final analysis. Of them 869 (73%) recovered renal function. Factors associated to recovery were age (p=0.01), presence of CKD (p=0.04), basal renal function (p<0.001), history of heart failure (p=0.02), having cognitive impairment (p=0.01), dependence (using Barthel index, p=0.002), renal function at admission (p<0.001), severity of AKI (p<0.001), blood pressure at admission (p=0.02) and hemoglobin at admission (p=0.04). Independent predictors of recovery were basal CKD-EPI (p<0.001), CKD-EPI at admission (p<0.001), severity of AKI (p=0.037), hemoglobin at admission (p=0.016), blood pressure at admission (p<0.001) and history of heart failure (0.001). After discharge, 46 (3%) patients died in the first 30 days. Associated factors to mortality were history of neoplasia (p=0.02), cognitive impairment (p<0.001), Barthel index (p<0.001) and the absence of renal recovery after AKI (defined as reaching a creatinine above 1.2 times of the baseline) (p=0.01). In an adjusted model, renal function recovery independently predicted short term mortality (HR 2.6, 95%CI [1.2-5.4], p=0.01). Conclusion: The absence of recovery after an AKI is an independent predictor of 30-day mortality.